Library Information System on Public Elementary School 108 Home Base Based on Android - Neneng Awaliah; Aida Justika; Aishiyah Saputri Laswi; Mansyur (Ceddi Journal of Education, 2022)
School libraries, especially elementary school libraries, as learning resources that contain various library instructions, can increase the interest in reading by school residents, especially teaching staff and students, and provide continuous opportunities to expand and deepen their knowledge. The purpose of the study is to build a web-based school library information system, especially in State Elementary School 108 Home Base, a system development method using Rapid Application Development (RAD). Based on the results of research on the Library Information System On Public Elementary School 108 Home Base Based On Android which has been built has good feedback for users because it makes it easier for users to borrow books at State Elementary School 108 Home Base, makes it easier for admins/officers to manage book lending data, book return data, and can help admins/library officers in the process of managing reporting in the library of State Elementary School 108 Home Base